Analyses of NOTCH3 variants in Chinese patients with clinically diagnosed Alzheimer's disease and frontotemporal dementia - Haitian Nan; Min Chu; Ailing Yue; Qianqian He; Jieying Li; Yanchen Liu; Lijun Chi; Xiaoyan Liu; Guoping Peng; Liyong Wu (Alzheimer’s Research & Therapy)
Abstract Background A pathogenic variant in the NOTCH3 gene has been identified as the cause of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). Studies focusing on variants in NOTCH3 in Alzheimer's disease (AD) and frontotemporal dementia (FTD) cohorts have been limited. We aim to screen clinically diagnosed AD and FTD patients with unknown etiology for pathogenic variants in NOTCH3 in the Chinese population. Methods This study included early-onset AD and FTD patients consecutively recruited from Xuanwu Hospital. We performed the whole exome sequencing of genomic DNA from the patients screened for rare, nonsynonymous, predicted deleterious NOTCH3 variants. The clinical characteristics of dementia patients with likely pathogenic NOTCH3 variants were described in detail. Results Three hundred four AD and 261 FTD patients were screened for variants in the NOTCH3 gene. Four cysteine-altering NOTCH3 variants—c.1630C > T,p.(R544C); c.1672C > T,p.(R558C); c.1759C > T,p.(R587C); and c.1918C > T,p.(R640C)—were identified as likely pathogenic variants according to ACMG guidelines. All four patients with cysteine-altering variants were clinically diagnosed with AD or FTD and presented with characteristic clinical manifestations and neuroimaging profiles. Notably, they also showed mild periventricular and deep white matter signal changes on neuroimaging. Our study showed a 0.7% (4/565) occurrence of NOTCH3 pathogenic variants in Chinese early-onset dementia patients. Conclusions Our findings expand the mutational and phenotypic spectrum associated with NOTCH3. NOTCH3 pathogenic variants are present in clinically diagnosed AD and FTD patients. However, the absence of biomarkers to confirm AD or FTD diagnoses limits the interpretation of whether these cases represent comorbid conditions or phenotypic overlaps with CADASIL. Clinical identification of dementia patients with these variants at an early stage is challenging.